The Influence of Tax Sanctions on Improving Compliance among Motor Vehicle Taxpayers: A Case Study of the Samsat Office in Bandung City, Indonesia - Purnamasari, Dyah; Sarii, Diana; Mulyatii, Yati (Journal of Ecohumanism, 2024)
This study is motivated by the observed shortfall in taxpayer compliance with Bumi and Bangunan Tax, prompting an evaluation of contributing factors. The primary aim is to assess the impact of Tax Sanctions on Motor Vehicle Taxpayer Compliance at the Bandung City SAMSAT Office. Employing a quantitative research design with a survey approach, the study analyzes the relationship between Tax Sanctions (independent variable) and Motor Vehicle Taxpayer Compliance (dependent variable) through regression analysis, utilizing SPSS for data evaluation. The findings reveal a significant positive effect of Tax Sanctions on taxpayer compliance, indicating that higher levels of enforcement correlate with improved compliance rates. This research contributes to the theoretical understanding of taxpayer behavior by reinforcing the role of sanctions in promoting compliance. Practically, it offers valuable insights for government policymakers, suggesting that enhancing tax sanction effectiveness can lead to increased compliance among motor vehicle taxpayers. These results underscore the importance of tailored enforcement strategies that not only deter non-compliance but also educate taxpayers about their obligations, ultimately fostering a more compliant tax environment.